ELECTRONIC DATA PROCESSING ON ACCOUNTING SOFTWARE - Anak Agung Gde Satia Utama; Dian Pratama (Galaxy International Interdisciplinary Research Journal, 2021)
Business or company operations will not be carried out if they do not utilize software applications. The utilization of accounting software has been widely applied to various sectors on a large and advanced scale. Complexity and significant change activity are possible to re-adjust system. The current system can be replace to accounting software. The objectives of this study are provide understanding, skill and knowledge in the use of accounting software. The activities method using virtual meeting by zoom. Updating information and focusing on the accounting software being studied will further increase participants’ understanding and be more helpful and add value to participants when entering the real world of work.